Gestão do desempenho e o modelo de gestão de pessoas: uma investigação em faculdades privadas com curso de administração em Fortaleza-CE - Muniz, Marcus Alessandre (2011)
Based on the principle that the research problem intrinsically involves difficulties between theory and practice, this dissertation sought to answer the following question: what is the relationship between people management and performance management of private colleges with courses in administration Fortaleza-CE? To obtain the response, the focus was not only identify the model of people management predominant, check the model performance management and human and organizational relationship between the processes. In this keynote, it was found that the model of people management prevalent in colleges in the sample model is the administrative specialist. Still, the perception of survey participants, the model of performance management was the predominant organizational management by objectives. Thus, the model human performance management, according to participants of the faculties of the sample, was the prevailing model of Lucena (1992). We sought to further the integration and the relationship between models of people management and organizational and human performance. The theoretical framework consists of the categories people management, organizational performance and human performance. The research was defined as the objectives and descriptive in nature and as to the procedures, such as literature, documentary and field. For data collection, were made available, via e-mail questionnaires to these goals. The nature of the data, the survey appears as quantitative and qualitative. The survey results show that the management programs of human performance, when used, are intended to improve the results of human resources in the organization, which provides also leveling with strategic planning, implementing criteria and indicators of performance management and can be considered well as improving the management process, interpersonal relationships and communication between the manager and his team.